Dynamics of Lauraceae trees and their Biomass in the 50-ha plot at Pasoh Forest Reserve, Negeri Sembilan, Malaysia - M.S. Nizam,; B. Norfazlina,; A. Latiff,; M.N. Nur Supardi, (Universiti Kebangsaan Malaysia, 2008)
A study was carried out to look at dynamics and above ground biomass of Lauraceae trees in the 50 ha plot at Pasoh Forest Reserve, Negeri Sembilan. Census data for the year 1985, 1990, 1995 and 2000 were obtained from the Forest Research Institute of Malaysia (FRIM), Kepong. The study was mainly focused on the year 2000 data; nevertheless, comparisons between each census year were carried out to look at variation between each census. Based on the year 2000 data, a total of 6,667 stems of Lauraceae were recorded, representing 11 genera and 49 species. The genera of Cryptocarya, Litsea and Beilschmiedia were abundantly present with 2,216 trees (33.24%), 1,769 trees (26.53%), and 673 trees (10.09%), respectively. Species-wise, Litsea magnifica showed the highest number of individuals of 916 trees (18 trees/ha). In general, distribution pattern analysis using Morisita’s Index of Dispersion (Id) showed a random distribution for this family with value Id = 1.02. Estimation of total above ground biomass of Lauraceae for the year 2000 was estimated at 39.71 t/ha. The genus of Litsea contributed the highest biomass with an estimation of 11.11 t/ha; species-wise, the Dehaasia cuneata indicated the highest biomass estimated at 5.16 t/ha. As a whole, the number of deaths of Lauraceae stems is greater than the number of new individuals recruited during the 15-year census whereby deaths mainly occurred among small individuals with diameter of 1.0-19.9 cm